Assessing the Effectiveness of Indonesia's Criminal Justice System in Combatting Corruption: A Juridical Analysis - Efendi, Razif Arfan; Sukasih, Arfianita (Institute for Law and Economics Studies, 2024)
This research conducts a comprehensive juridical analysis of Indonesia's criminal justice system concerning perpetrators of corruption crimes. The study evaluates the effectiveness of the existing legal framework, enforcement mechanisms, and outcomes in deterring and punishing corruption within the country. Utilizing qualitative research methods, including legal document analysis, case studies, and comparative analysis with anti-corruption measures in other countries, the research identifies strengths, weaknesses, and challenges within Indonesia's anti-corruption framework. Findings reveal that Indonesia possesses a robust legal framework for combating corruption, characterized by stringent penalties and specialized anti-corruption institutions such as the Corruption Eradication Commission (KPK) and specialized corruption courts (Tipikor). However, the effectiveness of this framework is compromised by resource constraints, political interference, legal loopholes, and institutional corruption. Despite successes in prosecuting high-profile cases and recovering assets, disparities in sentencing outcomes and conviction rates persist, reflecting systemic challenges within the criminal justice system. The research concludes by proposing recommendations to strengthen Indonesia's anti-corruption efforts, including enhancing institutional independence, allocating adequate resources, closing legal gaps, fostering transparency and accountability, and promoting public engagement and integrity.